Identifikasi Potensi Bahaya pada Stasiun Boiler Menggunakan Metode Hirarc di PT. Syaukath Agro - Hidjrawan, Yusi; Hartati, Rita; Marlinda, Marlinda; Ariansyah, Wanda (Jurnal Optimalisasi, 2024)
PT Syaukath Agro is a company operating in the Agribusiness Sector which is engaged in processing palm oil Fresh Fruit Bunches (FFB) into crude palm oil (CPO), Palm Kernel (PK) and shells. The palm oil processing system consists of several stages starting from receiving Fresh Fruit Bunches (FFB) to becoming palm oil or Crude Palm Oil (CPO). The palm oil processing process can be used in several stages carried out at each station. Based on interviews conducted, each station has a different level of risk of accidents, one of the stations that has a large risk of work accidents is the boiler station which is the heart of a palm oil factory where the steam boiler is the source of power and the source of the steam that will used to process palm oil. Boilers have potential dangers or risks when operated. The risks that often occur are falls, slips, burns, scalds, heat, noise, so it is very important to supervise and provide guidance regarding work safety. The size of the accident caused will certainly have a detrimental impact on the company. The severity of the accident can be determined through identification of potential dangers and risk assessment of all boiler operating activities at PT. Syaukath Agro. Based on the results of research conducted using the hirarc method, potential hazards found in boiler stations include: Unergonomic Working Attitudes, Noise Levels >84 dB with 8 Hours/Day Exposure, Working climate temperature (hot) 31°C on exposure >8 working hours/day, and oil buildup. Types of risk of work accidents at boiler stations consist of: Falls, injuries (slipping, slippery floors) Burns (in contact with hot objects around), Heat exhausting (Heat), Work accidents (fatigue ), hearing loss (noise), blisters (burns), health problems (muscles, bones), contact dermatitis (exposed to dangerous toxic radiation). Based on the results of risk control, it was found that the most appropriate type of control recommendation is administrative control and compliance with the use of personal protective equipment (PPE). Administration (Administration Control) is carried out by creating or providing a work system that can reduce the possibility of someone being exposed to potential dangers. The hierarchy of control of Personal Protective Equipment (PPE) is used to provide a boundary between exposure to the body and the potential danger received by the body.